Intraoperative Ultrasound Leads to Conservative Management of Benign Ovarian Tumors: A Retrospective, Single-Center Study - Badiglian-Filho, Levon; Menezes, Ademir Narciso de Oliveira; Faloppa, Carlos Chaves; Fukazawa, Elza Mieko; Mantoan, Henrique; Kumagai, Lillian Yuri; Baiocchi, Glauco (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To evaluate whether the use of intraoperative ultrasound leads to more conservative surgeries for benign ovarian tumors.Methods Women who underwent surgery between 2007 and 2017 for benign ovarian tumors were retrospectively analyzed. The women were classified into two groups: those who underwent intraoperative ultrasound (group A) and those who did not (group B). In group A, minimally-invasive surgery was performed for most patients (a specific laparoscopic ultrasound probe was used), and four patients were submitted to laparotomy (a linear ultrasound probe was used). The primary endpoint was ovarian sparing surgery (oophoroplasty).Results Among the 82 cases identified, only 36 met the inclusion criteria for the present study. Out of these cases, 25 underwent intraoperative ultrasound, and 11 did not. There were no significant differences in arterial hypertension, diabetes, smoking history, and body mass index for the two groups (p = 0.450). Tumor diameter was also similar for both groups, ranging from 1 cm to 11 cm in group A and from 1.3 cm to 10 cm in group B (p = 0.594). Tumor histology confirmed mature teratomas for all of the cases in group B and for 68.0% of the cases in group A. When the intraoperative ultrasound was performed, a more conservative surgery was performed (p < 0.001).Conclusion The use of intraoperative ultrasound resulted in more conservative surgeries for the resection of benign ovarian tumors at our center.
Keywords: intraoperative; laparoscopy; ovary; sparing; conservative surgery; ultrasound; oophoplasty